(untitled) (Western European Journal of Historical Events and Social Science, 2026)
Post-traumatic arthrosis is one of the most common chronic musculoskeletal disorders among athletes and develops as a consequence of joint injuries, repetitive overload, and insufficient rehabilitation. The condition significantly affects athletic performance, quality of life, and long-term functional capacity. Early diagnosis and comprehensive rehabilitation are essential for preventing disease progression and reducing disability risks. This article analyzes the main diagnostic approaches and rehabilitation strategies for post-traumatic arthrosis in athletes. Modern imaging techniques, clinical evaluation methods, laboratory analyses, and functional assessment tools are discussed